Sebreli, Juan José (1998). La era del fútbol. Editorial Sudamericana, Buenos Aires, 349 p. - Tallgren, Viveca (Diálogos Latinoamericanos, 2014)
Sebreli, Juan José (1998). La era del fútbol. Editorial Sudamericana, Buenos Aires, 349 p.